1996
DOI: 10.1021/es960046l
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Fractionation and Speciation in a Wetland System

Abstract: Selenium fractionation and speciation in Benton Lake National Wildlife Refuge (Montana), a wetland system containing moderate levels of selenium, were studied to determine the biogeochemical processes of selenium in wetlands. Results showed that selenate was a major selenium species of dissolved selenium in drainage water. It decreased substantially through the pond system as the relative percentages of organic selenium and selenite increased. Elemental selenium and selenium associated with organic materials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 32 publications
8
117
1
2
Order By: Relevance
“…The reduction of soluble selenate [Se(VI), SeO 4 2Ϫ ] and selenite [Se(IV), SeO 3 2Ϫ ] to the less toxic Se(0) converts selenium into an insoluble mineral form. In soils and sediments, this transformation is largely mediated by microorganisms (30,31,43,47), although abiotic reduction of selenium oxyanions can also occur in the presence of the Fe(II)-Fe(III) hydroxide mineral green rust (28). Anaerobic Se-respiring bacteria can use Se(VI) and Se(IV) as terminal electron acceptors and precipitate elemental selenium granules (26,29,30).…”
mentioning
confidence: 99%
“…The reduction of soluble selenate [Se(VI), SeO 4 2Ϫ ] and selenite [Se(IV), SeO 3 2Ϫ ] to the less toxic Se(0) converts selenium into an insoluble mineral form. In soils and sediments, this transformation is largely mediated by microorganisms (30,31,43,47), although abiotic reduction of selenium oxyanions can also occur in the presence of the Fe(II)-Fe(III) hydroxide mineral green rust (28). Anaerobic Se-respiring bacteria can use Se(VI) and Se(IV) as terminal electron acceptors and precipitate elemental selenium granules (26,29,30).…”
mentioning
confidence: 99%
“…It might imply that the increase of soluble Se in the low Se high organic matter soils is more pronounced than those in the high Se low organic matter soils upon drying. The stronger increase of soluble Se after drying found in our current work compared to those found by Zhang and Moore (1996) can thus be attributed to a more significant contribution of organic Se to total soluble Se in low Se high organic matter soils (samples in this study). Other studies also found that soluble Se in different extractions is mainly present as organic Se, especially in soils with low Se content, i.e.…”
Section: Drying Effect On Soluble Secontrasting
confidence: 52%
“…Differences between the observed and simulated data may be caused by difficulties in quantifying adsorption/desorption in the model. For example, absorption/desorption studies of selenite + selenate were done in freshwater (Zhang and Moore 1996) and may not be applicable to an estuarine environment.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ adsorption/desorption of selenite + selenate was modeled by the distribution coefficient K d 5 a9/b, where a9 is the intrinsic adsorption rate constant (L g 21 d 21 ), and b is the rate constant (d 21 ) of desorption (Nyffeler et al 1984). The value of K d was obtained from Zhang and Moore (1996), and values of a9 were obtained from Nyffeler et al (1984). The rate constant b was obtained by rearranging the K d equation to b 5 a9/ K d .…”
Section: Methodsmentioning
confidence: 99%